The Effect of Push Up Exercises and Rubber Springs on the Speed of Punching Gyaku Tsuki Dojo Bkc Kelet Jepara Regency (Indonesian Journal for Physical Education and Sport, 2022)
In karate matches, a punch is needed to attack your opponent or counter your opponent's attack. Gyaku tzuki is a straight punch attack aimed at the solar plexus which is opposite to the steps of the horses. Efforts to increase hand speed can be done with various kinds of exercises, for example training the speed of gyaku tsuki strokes using push ups and rubber springs. This research uses an experimental type. The design used in this study is the One-Group Pre-test-Post-test Design. The population on the research amounted to 10 athletes karate dojo BKC Keling. The sample in this research was 10 karate dojo BKC Keling Jepara district. The sampling technique used a total sampling technique. The results of this study indicate that the mean of the pretest data is 14.80, and the mean value of the posttest data is 22.60. As well as the table Paired Samples Correlations Sig value. is 0.236 or 23.6%, then there is a relationship between the pretest and posttest values of push-ups and rubber springs on the speed of the gyaku tsuki punch. The pretest percentage is 39.57% and the posttest percentage value is 60.43%. Based on the results of the research and discussion, it can be concluded that there is an effect of push-up exercises and rubber springs on the speed of the gyaku tsuki punch. The percentage of the effect of push-ups and rubber springs on the speed of the gyaku tsuki punch, namely the pretest 39.57% and the posttest 60.43%. The writer's suggestions for research 1) For trainers to increase the speed of gyaku tsuki punches with push-ups and rubber springs. 2) For athletes to have good and fast gyaku tsuki punch speed, it is necessary to increase training with push-ups and rubber springs to train muscle strength so that they have strong speed and punch.